Connections Beyond Campus: Ontario University Library Outreach Programs for High Schools - Buchansky, Heather (Partnership, 2021)
Over the past few decades, partnerships and programming between secondary school and post-secondary librarians and libraries have been widely discussed in library literature. These collaborations often exist to help high school students develop information literacy (IL) skills and to provide a smoother transition to university-level research. This paper examines the current high school outreach activities at Ontario university libraries that aim to bridge the gap between high school and post-secondary education. The purpose of this research, conducted through online surveys and interviews with academic librarians in the province, is to provide a snapshot of high school outreach activities and to highlight the benefits and challenges of such programming. It also examines why some libraries no longer offer such activities or programs. This analysis of the variety of outreach activities aims to generate discussion and ideas that academic libraries can use to connect with high school libraries.